THE EXISTENCE OF TRADE SECRETS AS DEBT COLLATERAL IN INDONESIA: ORIENTATION AND IMPLICATION - Yohanes Suhardin; Rolib Sitorus; Hendri Khuan; Sardjana Orba Manullang; Ade Sathya Sanathana Ishwara (Kanun Jurnal Ilmu Hukum, 2023)
This paper investigates the orientation and implications of using trade secrets as collateral, by analyzing legal regulations, case studies, and applicable legal approaches. The research method employed is a legal research method with a descriptive-analytical approach. Data sources include legal documents, court decisions, and relevant scholarly literature. The data is analyzed qualitatively to identify patterns, trends, and implications of using trade secrets as collateral in business transactions. This paper indicates that utilizing trade secrets as collateral has the potential to support companies in obtaining funding and maintaining financial stability. However, this involves complexities in assessing the value of trade secrets, legal protection, information security, and trust among parties involved. Laws safeguarding intellectual property rights and trade secrets are crucial in governing and safeguarding this mechanism. The use of trade secrets also has broad impacts, encompassing legal, economic, and business aspects. In Indonesia, Law Number 30 of 2000 concerning Trade Secrets provides a legal basis for the protection of trade secrets. However, the use of trade secrets as collateral requires strong cooperation among involved parties, a deep understanding of rights and obligations, and thoughtful strategic considerations.